Single-Entity Detection With TEM-Fabricated Nanopores - Yang, Hongcheng; Saqib, Muhammad; Hao, Rui (Frontiers in Chemistry, 2021)
Nanopore-based single entity detection shows immense potential in sensing and sequencing technologies. Solid-state nanopores permit unprecedented detail while preserving mechanical robustness, reusability, adjustable pore size, and stability in different physical and chemical environments. Transmission Electron Microscope (TEM) has evolved into a powerful tool to fabricate and characterize nanometer sized pores within solid-state ultrathin membrane. By detecting differences in the ionic current signals due to single entity translocation through the nanopore, solid-state nanopores can enable gene sequencing and single molecule/nanoparticle detection with high sensitivity, improved acquisition speed and low cost. Here we briefly discuss the recent progress in modification and characterization of TEM fabricated nanopores. Moreover, we highlight some key applications of these nanopores in nucleic acids, protein, and nanoparticle detection. Additionally, we discuss the future of computer simulations in DNA and protein sequencing strategies. We also attempt to identify the challenges and discuss the future development of nanopore detection technology aiming to promote the next-generation sequencing technology.